1998
DOI: 10.1016/s1097-2765(00)80035-0
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Brca2 in DNA Repair

Abstract: Abnormalities precipitated by a targeted truncation in the murine gene Brca2 define its involvement in DNA repair. In culture, cells harboring truncated Brca2 exhibit a proliferative impediment that worsens with successive passages. Arrest in the G1 and G2/M phases is accompanied by elevated p53 and p21 expression. Increased sensitivity to genotoxic agents, particularly ultraviolet light and methylmethanesulfonate, shows that Brca2 function is essential for the ability to survive DNA damage. But checkpoint act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
433
1
8

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 566 publications
(460 citation statements)
references
References 57 publications
18
433
1
8
Order By: Relevance
“…Only a single other codon 212 mutation is represented on the IARC database, this being TTT4TCT in a skin tumour. The recent demonstration that mouse ®broblasts with truncated BRCA2 are more sensitive to UV irradiation than controls (perhaps due to defective nucleotide or base excision repair) is clearly of interest in the context of this observation (Patel et al, 1998). Previous studies of sporadic breast cancer have revealed three codons at which mutation most commonly occurs: 175, 248 and 273 (Levine et al, 1994;Hollstein et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a single other codon 212 mutation is represented on the IARC database, this being TTT4TCT in a skin tumour. The recent demonstration that mouse ®broblasts with truncated BRCA2 are more sensitive to UV irradiation than controls (perhaps due to defective nucleotide or base excision repair) is clearly of interest in the context of this observation (Patel et al, 1998). Previous studies of sporadic breast cancer have revealed three codons at which mutation most commonly occurs: 175, 248 and 273 (Levine et al, 1994;Hollstein et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Tumorigenesis in carriers of germ-line mutations in BRCA1 and BRCA2 is invariably accompanied by loss of the wild-type allele (Smith et al, 1992;Neuhausen and Marshall, 1994;Collins et al, 1995;Gudmundsson et al, 1995;Kelsell et al, 1996) suggesting that the proteins encoded by the two genes operate as tumour suppressors. An increasing-body of evidence favours a role for both BRCA1 and BRCA2 in cellular response to DNA damage (Connor et al, 1997;Scully et al, 1997;Patel et al, 1998). It is postulated that the BRCA genes act as caretakers, functioning to maintain genomic stability, rather than as gatekeepers which regulate cellular proliferation (Brugarolas and Jacks, 1997;Kinzler and Vogelstein, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Germline mutations in the breast-cancer susceptibility gene BRCA2 confer susceptibility to familial early-onset breast and ovarian cancers (Wooster et al, 1994(Wooster et al, , 1995Tavtigian et al, 1996;Brody and Biesecker, 1998;Rahman and Stratton, 1998). Extensive studies have indicated that BRCA2 has an important function in DNA repair (Connor et al, 1997;Mizuta et al, 1997;Sharan et al, 1997;Wong et al, 1997;Chen et al, 1998;Patel et al, 1998). Recent reports indicate that BRCA2 acts in the homology-directed recombinational repair of double-strand DNA breaks (Davies et al, 2001;Moynahan et al, 2001;Xia et al, 2001;Kraakman-van der Zwet et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also suggest that this complex may function in the cellular response to DNA damage (Connor et al, 1997a;Scully et al, 1997a,b;Patel et al, 1998). As noted above, the primary sequences of BRCA1, BARD1 and BRCA2 are poorly conserved in mammals (mouse/human identities of *57%, 70% and 58%, respectively) and orthologs of these polypeptides are conspicuously absent from at least one lower eukaryote: the budding yeast S. cerevisiae.…”
mentioning
confidence: 98%